2007
DOI: 10.1002/adsc.200600536
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Decarboxylative Addition of Malonic Half Thioesters to Imines

Alfredo Ricci,
Daniel Pettersen,
Luca Bernardi
et al.

Abstract: We describe a biomimetic organocatalytic enantioselective decarboxylative addition of malonic acid half thioesters to imines. This simple protocol makes use of readily available Cinchona-derived organocatalysts and nucleophiles at the carboxylate oxidation state. The resulting b-amino thioesters, being attractive precursors for the preparation of optically active b-amino acids, are formed in good yields and in up to 79 % ee. As suggested by several mechanistic insights the desired products are formed via initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…The proposed addition–decarboxylation sequence is consistent with current mechanistic understanding [31,35,3738]. However, we cannot exclude an alternative decarboxylation–addition pathway at this stage.…”
Section: Introductionsupporting
confidence: 87%
“…The proposed addition–decarboxylation sequence is consistent with current mechanistic understanding [31,35,3738]. However, we cannot exclude an alternative decarboxylation–addition pathway at this stage.…”
Section: Introductionsupporting
confidence: 87%
“…For example, this process generally employs an ester equivalent, such as a malonic acid half oxyester or thioester, to participate in the reaction under very mild conditions and thereby circumvent the problems with strong bases and self‐condensation. Catalytic asymmetric decarboxylative Mannich reactions with a wide range of aldimine‐based electrophiles have proven to be highly effective 46. However, expansion of the electrophilic acceptors to ketimines for the synthesis of β‐amino esters with a quaternary stereogenic center seems to be more challenging, since controlling the ketimine geometry in combination with the π‐facial selectivity of electrophilic attack is critical for the stereochemical outcome.…”
Section: Screening Of Catalysts and Conditions Optimization For The Dmentioning
confidence: 99%
“…In contrast, Nature does not rely on metal ions for generation of malonic acid half-thioesters (MAHTs) enolates that are used in the biosynthesis of fatty acids and polyketides in all kingdoms of life [64,65]. Inspired by naturally occurring enzymatic polyketide biosynthesis, proceeding through the decarboxylative generation of thioester enolates, the first straightforward organocatalytic enantioselective decarboxylative addition of MAHTs 11 to imines resulting in optically active 3 -amino thioesters, obvious precursors of important 3 -amino acids, has been recently devised [66]. A screening of chiral catalysts derived from Cinchona alkaloids and of reaction conditions, revealed that the use of catalyst XIV [67] gave the best results in terms of enantioselectivity and yields.…”
Section: Enolate Generation By Decarboxylation: Malonic Acid Half Thimentioning
confidence: 99%